2006
DOI: 10.1094/pd-90-0061
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Variability of Begomoviruses in Tomato from the Andean States of Venezuela

Abstract: The three Andean states of Mérida, Táchira, and Trujillo in Venezuela produce tomatoes (Lycopersicon esculentum) year-round with a high frequency of virus-like symptoms. Polymerase chain reaction amplification using degenerate primers detected begomoviruses in 18% of leaf samples collected from tomato plants showing virus-like symptoms in commercial fields in these states between 1993 and 1994. A comparison of the sequences of the amplified DNA products revealed a diversity of begomovirus sequences in tomato p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
2
14
0
1
Order By: Relevance
“…We did in fact observe that some of the begomovirus negative samples contained other viruses, which will be reported elsewhere. In a survey carried out in tomato crops in Venezuela between 2003 and 2004, begomoviruses were detected in approximately 18% of samples collected from plants with virus-like symptoms [21], which was similar to our results. It is interesting to note that symptom analyses of the positive samples confirmed that there was no clear correlation between type of symptom (interveinal chlorosis, rugosity, yellow mosaic, leaf distortion, and stunting) and the corresponding virus species (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…We did in fact observe that some of the begomovirus negative samples contained other viruses, which will be reported elsewhere. In a survey carried out in tomato crops in Venezuela between 2003 and 2004, begomoviruses were detected in approximately 18% of samples collected from plants with virus-like symptoms [21], which was similar to our results. It is interesting to note that symptom analyses of the positive samples confirmed that there was no clear correlation between type of symptom (interveinal chlorosis, rugosity, yellow mosaic, leaf distortion, and stunting) and the corresponding virus species (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…2). This result could be expected due to the traffic of tomato seedlings across the country as was previously observed for Potato yellow mosaic virus (Nava et al 2006;Chirinos et al 2014;Geraud-Pouey et al 2015). According to our results MeMV has a relative high genetic diversity in Venezuela compared to other begomoviruses widespread in the country, like Melon chlorotic mosaic virus (MeCMV), which has a low genetic diversity (NI > 97 %), even when analysing the full DNA-A component .…”
supporting
confidence: 85%
“…(Convolvulaceae) in Puerto Rico (Brown et al 2001) and, afterwards, was reported in Belize (GenBank accession numbers for DNA-A components: EU709521; EU709522; EU709525), Saint Kitts and Nevis, (GenBank accession number for DNA-A component: GU320575) and Venezuela (GenBank accession number for DNA-A component: AY50899). In the latter case, the virus was found infecting tomatoes and named Btomato mosaic leaf curl virus^ (Nava et al 2006). However, this isolate is currently considered as an isolate into the species MeMV (Brown et al 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dada las similitudes en genomas, circunstancialmente aquí adoptamos el nombre de Tomato Venezuela virus para nuestro aislado. Nuevos Begomovirus han sido detectados en la zona andina venezolana (Nava et al 2006). Recientemente, fue encontrado también el Tomato yellow leaf curl virus (TYLCV) como primer reporte para Venezuela, incluso para Sudamérica (Zambrano et al 2007).…”
unclassified